Performance Paradigm: Entrepreneurial Good University Governance Mediating Leadership Style in State Universities - Hadiwidjaja, Rini Dwiyani; Suroso, Arif Imam; Siregar, Hermanto; Sailah, Illah (Pandawan, 2024)
This study examined the influence of Entrepreneurial Good University Governance (EGUG) on Service Performance (SEV), Financial Performance (FIN), and Sustainability Performance (SUS), with Leadership Style (LS) as a mediating variable in State University of Public Service Agency (SU-PSA) in Indonesia. A quantitative approach was applied, involving 64 respondents, and data were analyzed using the SEM-PLS method. The findings revealed that EGUG significantly impacted service, financial, and sustainability performance. Leadership style also had a substantial effect, partially mediating the relationship between EGUG and performance outcomes. EGUG influence on performance was both direct and indirect through leadership style. The novelty of this study lies in extending Good University Governance to include EGUG, which fosters innovation, financial sustainability, and public service. Practical examples, such as the Bandung Institute of Technology, illustrate how entrepreneurial governance enhances financial independence and strengthens industry ties. Similar models have been adopted in the United States and Europe, where entrepreneurial governance supports academic excellence and contributes to regional economic development. This approach offers a flexible governance model for other institutions to address their unique challenges. However, the relatively small sample size of 64 respondents limits the generalizability of the findings. The specific focus on SU-PSA under the Ministry of Education, Culture, Research, and Technology may not fully represent other university types. Future studies should expand the sample and include a broader range of universities to enhance the robustness and applicability of the results.